Case report: Intraosseous hibernoma (IOH) mimics osseous metastasis: another rare pitfall in FDG-PET-CT - Stolte, Sebastian J.; Geiger, Hanna; Forrer, Flavio; Rodriguez, Regulo; Müller, Joachim (Frontiers in Nuclear Medicine, 2023)
Intraosseous hibernoma (IOH) mimicking osseous metastasis is a rare and little-known pitfall in nuclear medicine and radiology. Referring to a clinical case, we show imaging features in FDG-PET and CT as well as pathological characteristics and discuss MRI and differential diagnoses. A 73-year-old woman was assigned for an FDG-PET/CT examination after the incidental finding of a suspicious pulmonary nodule. The FDG-PET/CT examination detected a small slightly FDG-avid pulmonary nodule suspicious for malignancy and a small slightly sclerotic lesion with mild FDG-uptake in the upper pubic bone. Histopathology revealed an intraosseous hibernoma, a rare benign soft-tissue tumor arising from brown fat. In the sparse literature available, intraosseous hibernomas may or may not be positive on bone scans. As in our case, most are slightly sclerotic on CT but lytic lesions have also been described. On MRI, they are T1 hypointense to subcutaneous fat and hyperintense to skeletal muscle; they are usually T2 hyperintense and may show peripheral contrast enhancement. According to the literature, IOHs are mostly incidental findings with solitary lesions in the spine, pelvis, ribs, or, very rarely, in the extremities with low to moderately increased glucose metabolism. IOHs present as painless tumors in general; a few painful cases could be successfully treated with radiofrequency ablation or surgery. Differential diagnoses include metastases, lymphoma, fibrous dysplasia, and non-ossifying fibroma among others. Intraosseous hibernoma is a rare benign tumor that can mimic metastases in FDG-PET, CT, bone scan, and MRI. IOHs might be indistinguishable from metastases or malignant lesions, which makes a biopsy or follow-up mandatory in clinically relevant cases. Given the benign nature of IOHs, radiofrequency ablation or surgery is only an option in symptomatic cases.